If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + -29 = 5x + 7 Reorder the terms: -29 + -6x = 5x + 7 Reorder the terms: -29 + -6x = 7 + 5x Solving -29 + -6x = 7 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -29 + -6x + -5x = 7 + 5x + -5x Combine like terms: -6x + -5x = -11x -29 + -11x = 7 + 5x + -5x Combine like terms: 5x + -5x = 0 -29 + -11x = 7 + 0 -29 + -11x = 7 Add '29' to each side of the equation. -29 + 29 + -11x = 7 + 29 Combine like terms: -29 + 29 = 0 0 + -11x = 7 + 29 -11x = 7 + 29 Combine like terms: 7 + 29 = 36 -11x = 36 Divide each side by '-11'. x = -3.272727273 Simplifying x = -3.272727273
| -2C+8=24 | | 5x^8+30x^6-35x^4=0 | | -97-8x=10x+137 | | 45=80-y | | 3(x+2.93)=2x | | 45=111-y | | 9+x^2= | | 6250(4x)=10 | | 4=log(5X-70) | | 18x^2+21x=-6 | | -3(1+h)=.33(3-12h) | | x-2y+z=4 | | 38=17-y | | -36+24-3=y | | 9x^2-1=80 | | 80y=4w+5x | | x-2y+4=4 | | 140n^3+40n^2-35n-10=0 | | 17=9y | | 4(2x-3)-3(5x+4)=7x(5x-4) | | x+x^2+1=0 | | 6x+52=2x+88 | | -.2f+.8f+21=6 | | 6.7a+15=82 | | 53.7q+1.2=386.2-1.3q | | sqrt(u-5)=6 | | 5.44=.34a | | 5(3x-7)-7=5(x-2)+28 | | -6250+(4x)=-10 | | 12x^2-52x+80=0 | | 2x=x^2-6x+7 | | 50v^3+10v^2-40v-8=0 |